Rethinking the English Effect (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is about new pedagogical technologies in teaching EnglishWhen talking about the importance of recovery, mastering the science is a bit difficult. The analysis of the student, taking into account the complexity organization. From the new methods of increasing the language example, its significance is revealed.